SEX DIFFERENCES IN THE ANTERIOR ACETABULAR RIDGE MORPHOLOGY - Fidel O. Gwala; Jeremiah Munguti; Kevin Ongeti; Kirsteen Awori (Asociación Argentina de Anatomía Clínica, 2020)
Objectives: The anterior acetabular ridge morphology, an important consideration in the design of hip prosthesis, shows marked interethnic variability. There is however a paucity of local data highlighting the prevalence of the various anterior acetabular ridge shapes. Furthermore, sex-related differences have hardly been documented. Therefore, this study aimed to determine the shapes of the anterior acetabular ridge in a sample Kenyan population and the sex differences therein. Methods: Ninety-four paired hip bones (44 female, 50 male) from the osteology collection at the National Museums of Kenya were studied. The shape of the anterior acetabular ridge was determined and recorded. Results: The anterior acetabular ridge was curved in 34% of cases, straight in 24.5%, angular in 21.3% and in irregular 20.2% of the cases. The curved type was more frequent in females (50.0%) compared to males (20.0%). Conclusion: Sexual dimorphism influences anterior acetabular ridge morphology and which should be borne in mind during acetabular reconstructive procedures and design of acetabular prosthesis.